Factors influencing online purchase intention of millennials and gen z consumers - Nasrul Fadhrullah Isa; Sharifah Nurafizah Syed Annuar; Imelda Albert Gisip; Nelson Lajuni (Journal of Applied Structural Equation Modeling, 2020)
This study examines the factors affecting millennials and generation Z’s purchase intention in online shopping. The variables under investigation, namely, impulse purchase orientation, quality orientation, brand orientation, online trust, and online purchase experience, were tested. The data collection approach used a web-based questionnaire that was created and distributed to 584 university students in Malaysia. Data were analyzed via the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach to examine the posited research hypotheses. The results revealed that impulse purchase orientation was the strongest predictor of consumers’ online purchase intention in Malaysia. This is followed by online trust, and the online purchase experience and quality orientation. Meanwhile, brand orientation did not affect customers’ intention to purchase online. The results contribute new and extensive inputs into the marketing theory and expand the emergent literature on consumer intention to shop online in Malaysia, whereby rich multi-ethnic cultures should be fully exploited. Future directions are offered.